Management of idiopathic pulmonary fibrosis and pulmonary hypertension - Schulze, K. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF) is an untreatable diffuse parenchymal lung disease with a median survival of approximately three years. Pulmonary hypertension (PH) is frequently seen in patients with IPF and is commonly attributed to hypoxic vasoconstriction and capillary destruction. Pathology findings include endothelial proliferation and medial hypertrophy that exceed those expected in the setting of hypoxia. Non-invasive evaluation has limited sensitivity and specificity for the diagnosis of PH in IPF; therefore, right-heart catheterisation remains the ‘gold standard’ diagnostic test. PH in patients with IPF is associated with decreased exercise capacity and worse survival. Given the grave consequences of this condition, treatment of PH could improve functional outcomes and survival. However, possible treatments such as long-term supplemental oxygen and targeted vascular therapy are either unstudied or remain unproven.